Fundamental free-space solutions of a steady axisymmetric MHD viscous flow. Issue 1 (3rd March 2016) - Sellier, A.; Aydin, S. H.
Abstract : This work obtains the velocity and pressure fields of two fundamental axisymmetric MHD viscous flows of a conducting Newtonian liquid due to axial and radial distributions of forces on a ring in the presence of a uniform axial magnetic field The worked out procedure rests on the analytical determination of the pressure and of some of the Cartesian velocity components of another general three-dimensional fundamental MHD flow. The derived axisymmetric fundamental flows are found to deeply depend upon the nature (axial or radial) of the forces distributed on the ring, the ring size and the Hartmann layer thickness This is illustrated by computing a few flow patterns using a suitable numerical treatment.